Probing charge transfer characteristics in a donor–acceptor metal–organic framework by Raman spectroelectrochemistry and pressure-dependence studies. Issue 40 (4th October 2018) - Usov, Pavel M.; Leong, Chanel F.; Chan, Bun; Hayashi, Mikihiro; Kitagawa, Hiroshi; Sutton, Joshua J.; Gordon, Keith C.; Hod, Idan; Farha, Omar K.; Hupp, Joseph T.; Addicoat, Matthew; Kuc, Agnieszka Beata; et al.
Abstract : Donor–Acceptor Metal–Organic Frameworks display redox and pressure dependent charge transfer properties. Abstract : The stimuli responsive behaviour of charge transfer donor–acceptor metal–organic frameworks (MOFs) remains an understudied phenomenon which may have applications in tuneable electronic materials. We now report the modification of donor–acceptor charge transfer characteristics in a semiconducting tetrathiafulvalene–naphthalene diimide-based MOF under applied electrochemical bias and pressure. We employ a facile solid state in situ Raman spectroelectrochemical technique, applied for the first time in the characterisation of electroactive MOFs, to monitor the formation of a new complex TTFTC˙ + –DPNI from a largely neutral system, upon electrochemical oxidation of the framework. In situ pressure-dependent Raman spectroscopy and powder X-ray diffraction experiments performed in a diamond anvil cell revealed blue shifts in the donor and acceptor vibrational modes in addition to contractions in the unit cell which are indicative of bond shortening. This study demonstrates the utility of in situ Raman spectroscopic techniques in the characterisation of redox-active MOFs and the elucidation of their electronic behaviours.